Kraft lignin and polyethylene terephthalate blends: effect on thermal and mechanical properties - Lívia Lazzari; Eloilson Domingos; Letícia Silva; Alexei Kuznetsov; Wanderson Romão; Joyce Araujo (Polímeros, 2020)
Abstract In this work, bottle-grade poly(ethylene terephthalate) (PETR), kraft lignin (KL), and chemically modified lignin (ML) were used to form blends to improve the mechanical and thermal properties of pure PET. The PET/KL and PETR/ML blends were produced with 0.5, 1, 3, and 5 wt.% of lignin via melt extrusion and injection molding. The produced blends and PETR were characterized by Fourier transform infrared spectroscopy (FTIR), thermogravimetry (TGA), differential scanning calorimetry (DSC) and mechanical properties testing. The FTIR measurements confirmed the chemical modifications of the ML samples, while the TGA results showed KL to be thermally more stable than ML. The glass transition temperature of PETR changed as a function of the amount of lignin, as revealed by the DSC measurements. The PET/KL blends demonstrated their potential for use as an engineering material due to their improved thermal and mechanical properties compared to those of PETR.